Nursing Care of the Client with Dengue Fever: Nepal Perspective - Singh, Ajanta (Journal of Nursing Education of Nepal, 2023)
Dengue is an acute viral illness caused by RNA virus of the family Flaviviridae and spread by Aedes  mosquitoes. Presenting features may range from asymptomatic fever to dreadful complications such  as hemorrhagic fever, shock associated with other symptoms of muscles and joint pain, cutaneous rash  etc. Early and accurate diagnosis is critical with good nursing care and vigilant treatment may reduce  the mortality. Although dengue virus infection is usually self-limiting, it has come up as a public health  challenge in our country. This paper has the synthesis of reviews with short epidemiology, transmission cycle, clinical and  laboratory diagnosis, surveillance, prevention and nursing care. The content has been extracted from  various reports and publications through online access and also reviewed the national guidelines of  Nepal.
Keywords: Dengue; Hemorrhagic fever; Nursing care; Prevention and Control